External Morphology of Tagosodes orizicolus (Homoptera: Delphacidae) Revealed by Scanning Electron Microscopy - Mora Castro, Rebeca (2001)
A comprehensive analysis of the ultrastructure of the delphacid rice pest Tagosodes orizicolus (Muir) was undertaken using scanning electron microscopy to resolve taxonomic problems in the distinction of females and nymphs from other specimens commonly found in rice Þelds of tropical America. This research includes a detailed description of female genitalia and the ultrastructural variations observed during nymphal development. Ultrastructure of the mouthparts, speciÞcally the stylets; and the genitalia of the male are also described. Important ultrastructural details were revealed, such as the presence of microtrichia and sensillae, which are not clear when observed by light microscopy. The adults have numerous sensillae; immatures have bell-shaped chemoreceptors along the dorsal area, structures that are absent in the adult stage. Strong differences were observed between the Þrst instar and older nymphs, such as stamen-like setae, wider frons, convex clypeus observed in the Þrst and second instars; whereas conical eyes and an oar-shaped legs were observed only in the Þrst instar.